Permainan Hydrocarbon Craft sebagai Media Pembelajaran untuk Meningkatkan Motivasi Belajar dan Keterampilan Berpikir Kritis Peserta Didik pada Materi Senyawa Hidrokarbon - Ma'rufah, Nadia Izaty; Lutfi, Achmad (UNIB Press, 2026)
This study aims to obtain a Hydrocarbon Craft game that meets the feasibility aspects based on the valid, practical, and effective categories in improving students' learning motivation and critical thinking skills on hydrocarbon compounds. This study uses the Research and Development (R&D) type of research that refers to the ADDIE development model. However, this study is limited to the development stage. The product trial was conducted on a limited basis with 33 grade XI students at SMA Khadijah Surabaya. The instruments used were validation sheets, student response questionnaires, student activity observation sheets, learning motivation questionnaires based on the ARCS model developed by Keller, which includes four components, namely Attention, Relevance, Confidence, and Satisfaction and pretest-posttest sheets. The following are the details of the research results obtained, namely (1) the validity aspect obtained a mode of 5 with a very valid category, (2) the practicality aspect was obtained through a student response questionnaire with a percentage of 95.43% and observation of student activities of 88.25% so that the media was said to be very practical, (3) the effectiveness aspect was obtained through a learning motivation questionnaire of 90%, and the results of the posttest of critical thinking skills analyzed using the Wilcoxon Signed Ranks Test obtained a p value <0.05 which showed that there was a significant difference between the pretest and posttest scores, so that the media was said to be effective. Based on the research results obtained, it shows that the Hydrocarbon Craft game is suitable for use as a learning medium to increase learning motivation and critical thinking skills of students in the material of hydrocarbon compounds.